Pelatihan bagi Guru SMP Negeri 3 Taman Kabupaten Pemalang dalam Menerapkan Authentic Assesment - Nizaruddin, Nizaruddin; Roshayanti, Fenny; Sutrisno, Sutrisno; Fajriyah, Khusnul; Muhtarom, Muhtarom (Perkumpulan Kualitama Edukatika Indonesia, 2025)
This Community Service (PKM) activity takes the form of training to enhance the teachers of SMP Negeri 3 Taman, Pemalang Regency, in implementing authentic assessment in learning. This community service aims to provide teachers with understanding and experience in compiling authentic assessment instruments. This PKM activity is carried out using an andragogy approach, namely through training, followed by assignments, and mentoring. The training material is presented with a greater emphasis on practice than theory, featuring a ratio of 25% theory and 75% practice. Community service activities on authentic assessment have successfully improved the understanding of SMP N 3 Taman teachers regarding the importance of authentic assessment in the learning process. Before participating in the community service, teachers’ knowledge of authentic assessment was still limited; however, after attending the training, they demonstrated a deeper understanding of the concept, objectives, and techniques for implementing authentic assessment in the educational context. This increase in understanding indicates that this community service has been successful in providing new insights to teachers regarding the importance of using more authentic assessments, which include portfolio-based assessments, projects, and case-based assessments.